Systematic Literatur Review : Pengaruh Solvabilitas dan Corporate Social Responsibility (CSR) terhadap Manajemen Laba pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Tahun 2018-2020 - Selpi Julianti; Risti Ayu Mawarni; M Reja Dwi Pranoto (Universitas 45 Surabaya, 2026)
Earnings management is an important issue in financial reporting because it can reduce the quality of accounting information and mislead stakeholders in their decision-making. This practice is often associated with a company's financial condition and non-financial mechanisms such as Corporate Social Responsibility (CSR). This study aims to analyze the effect of solvency and Corporate Social Responsibility (CSR) on earnings management in manufacturing companies in the consumer goods industry through a Systematic Literature Review (SLR) approach. The SLR method was used to collect, select, and synthesize relevant previous research results published between 2018 and 2020. The results of the study indicate that solvency, which is generally measured by the Debt to Equity Ratio (DER), has a diverse relationship with earnings management, depending on the company's profitability and financial pressure. Meanwhile, CSR tends to act as a control mechanism that can suppress profit management practices by increasing corporate transparency and legitimacy, although in some studies CSR is also used opportunistically. These findings indicate that the influence of solvency and CSR on profit management is contextual and influenced by other factors such as profitability and corporate governance.